The association between sleep disorder, sleep duration and chronic back pain: results from National Health and Nutrition Examination Surveys, 2009-2010 - Meiru Zhong; Zhou Wang (BMC, 2024)
Abstract Background Back pain is a typical condition, and the association among sleep disorders, sleep duration and back pain is currently being investigated. The purpose of this research is to explore the connection between sleep disorders, sleep duration and chronic back pain as well as confounding factors. Methods Our data were obtained from the National Health and Nutrition Examination Survey (NHANES) data set of the USA and 1,131 participants were included in the study. Multivariable logistic regression was employed to investigate the relationship between sleep disorders, sleep duration and chronic back pain. And subgroup analysis conducted by gender, age, race, education, marital status, PIR, BMI, awakening events, hypertension condition and diabetes condition was also performed. Results Our study includes 1131 participants, 513 are men (45.4%) and 618 are women (54.6%), 151 participants with sleep disorders (13.4%) and 980 participants without (86.6%). The fully adjusted model with adjustment variables including age, gender, race, BMI, PIR, drink, smoke, education, marital status, awakening conditions, hypertension, diabetes and part of back pain constructed through multiple logistic regression shows that chronic back pain is associated with sleep disorders [OR = 3.71, 95% CI: (1.25, 10.99), p < 0.05]. Using normal sleep duration as a reference, there is no statistical difference between short sleep duration [OR=-0.35, 95% CI: (-0.95, 0.24), p = 0.241], long sleep duration [OR = 0.81, 95% CI: (-1.61, 3.24), p = 0.513] and chronic back pain. It can be found through subgroup analysis that age between 40 and 60 years, age larger than 60 years, different race, marital status and BMI >30 kg/m2 are associated with chronic back pain and sleep disorders. We also find a nonlinear relation which is likely to be rotated S-shape among chronic back pain and sleep duration by fitting smooth curves. Conclusion Our results suggest a substantial positive relationship between chronic back pain and sleep disorders and there is no statistical association between sleep duration and chronic back pain. The findings drawn from our study provide a basis for future exploration of the causal association between chronic back pain and sleep disorders, and provide references for timely elimination of interfering factors.